The Urgency of Islamic Religious Education in Shaping Students' Emotional Intelligence at SMP Al-Wasliyah 31 Medan - Arsitah, Dilah; Najwa, Syailla; Zalianti, Nurliza; Fadilah, Fiqih (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2025)
Islamic Religious Education (IRE) plays a crucial role in shaping students' emotional intelligence, particularly at the junior high school level. Emotional intelligence includes the ability to recognize, understand, and manage one's own emotions as well as those of others, which significantly impacts students' social interactions and academic success. This study aims to analyze the urgency of IRE in shaping students' emotional intelligence at SMP Al-Wasliyah 31 Medan. The research employs a qualitative approach using interviews, observations, and document analysis. The findings reveal that IRE significantly contributes to enhancing students' self-awareness, emotional regulation, empathy, and social skills. Therefore, integrating religious values into education is a crucial aspect of developing students' character and emotional intelligence.